About Current Issues Of Training Modern Creative Instructors Of Preschool Educational Institutions - Saidalikhodjaeva Nilufar Faxriddinovna (Genius Journals, 2024)
The article examines the specific pedagogical and psychological features of preparing future preschool education specialists for innovative professional activities. The semantic aspects characterizing the process of creativity in the work of a teacher, as well as the criteria characterizing this process are highlighted. It also analyses best teaching practices and collaboration with parents to prepare future early childhood educators for their innovative careers
Keywords: preschool education; preschool education specialist; creative approach